Myocardial blood flow, oxygen extraction and consumption, and efficiency in elite endurance athletes and control subjects at rest - Heinonen, I.; Kudomi, N.; Kemppainen, J.; Luotolahti, M.; Sipilä, H.; Duncker, D.; Knuuti, J.; Kallioski, K. K. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
In our previous study we reported that pronounced left ventricle (LV) hypertrophy shows neither impaired or supranormal blood flow reserve (Heinonen et al. 2008 J Physiol). In the present study we aimed to elucidate the characteristics of athlete`s heart further by applying [15O]-labelled radiotracers and positron emission tomography and measured myocardial blood flow (MBF), oxygen extraction (MOE) and consumption (MVO2), and efficiency in 13 highly trained male endurance athletes and 13 control subjects at rest and during supine cycling exercise (100 watts) by established methods and principles (Iida et al. 1996 Circulation; Laine et al. 1999 Circulation). Cardiac ultrasound was also performed and radial artery was cannulated for measurements of arterial oxygen content and energy substrates. Many of athletes (30 ± 5 yrs) whose VO2max in bicycle test was 60 ± 3 ml/kg/min, had participated in Olympics and various World cups in running, CC-skiing, cycling and walking, but control subjects (30 ± 5 yrs, VO2max 40 ± 5 ml/kg/min) exercised regularly less than three times per week. LV mass (138 ± 18 g/m2, p<0.001) was higher and LV workload (1.6 ± 0.5 and 4.1 ± 1.0 mmHg/mL/min/g, p<0.01 in both) and MBF (0.9 ± 0.4 and 1.8 ± 0.4 ml/g/min, p=0.51 at rest and <0.01 during exercise) were lower in athletes both at rest and during exercise, respectively, compared to untrained men (93 ± 12 g/m2, 2.5 ± 0.9 and 7.1 ± 2.0 mmHg/mL/min/g, 1.2 ± 0.3 and 2.3 ± 0.4 ml/g/min, respectively). MOE increased in response to exercise in both groups, but was also always higher in athletes (71 ± 22 vs. 63 ± 11 % at rest and 88 ± 11 vs. 73 ± 10 % during exercise, respectively, both p<0.05). As a result, MVO2 per gram of myocardium was similar between athletes and controls both at rest and during exercise (0.12 ± 0.06 and 0.32 ± 0.08 ml/g/min in athletes and 0.15 ± 0.05 and 0.35 ± 0.08 ml/g/min in controls). Myocardial efficiency was similar between the groups at rest (13.4 ± 11.5 % in athletes and 12.3 ± 2.8 % in controls), but was significantly lower in athletes during exercise (9.7 ± 3.6 % vs. 14.3 ± 5.1 %, p<0.05). Arterial glucose was essentially comparable between the groups, but arterial free fatty acids were significantly higher in athletes at rest and especially during exercise (0.42 ± 0.23 vs. 0.25 ± 0.16 mmol/L), and lactate increased only in control subject in response to exercise (from 1.0 ± 0.2 to 2.8 ± 1.3 mmol/L). In conclusion, elite endurance athletes have lower myocardial blood flow, higher oxygen extraction, but unchanged oxygen consumption at rest and during exercise. Moreover, it is likely that higher arterial free fatty acid levels, and thus their utilization, partly explains the noticed lower myocardial efficiency during applied exercise low for elite athletes but demanding for untrained control subjects.